Participants' experience and perceptions of the Future Search Conference as an organizational change strategy in the Nursing Board of Namibia - Layne, Nelao (Rhodes University, Faculty of Education, Department of Education, 2006)
Future Search is a new concept in Namibia. This study looks at the application of a Future Search Conference (FSC) with the Nursing Board of Namibia with a view to investigating participants' experiences and perceptions of the FSC as an organizational change strategy. I conducted a case study in the interpretive paradigm, since I was interested in understanding the subjective experience and individual perceptions of five respondents with regard to the FSC. To obtain in-depth information on how participants felt about the FSC, I employed two data gathering tools: un-structured individual interviews and observation. The findings confirmed that the Future Search is a new concept in the Ministry of Health in particular and in Namibia as a whole. Participants are of the opinion that leaders and managers are key figures in the success or failure of the Future Search. They showed a tremendous interest in the process and are willing to embrace and master the tool so they could try it in their various areas of work. Emphasis was put on the need to get the FSC introduced to leaders and higher management cadres on a wider scale, because they are decision makers and can decide whether or not the Future Search could be institutionalized. This study concludes with an appeal from respondents to be exposed to the Future Search again in a better time frame than the short time we had.
Keywords: Organizational change -- Namibia; Nursing -- Study and teaching -- Namibia